Alcohol taxes' contribution to prices in high and middle‐income countries: Data from the International Alcohol Control Study. (22nd November 2017) - Wall, Martin; Casswell, Sally; Callinan, Sarah; Chaiyasong, Surasak; Viet Cuong, Pham; Gray‐Phillip, Gaile; Parry, Charles D. H.
Abstract: Introduction: Taxation is increasingly being used as an effective means of influencing behaviour in relation to harmful products. In this paper we use data from six participating countries of the International Alcohol Control Study to examine and evaluate their comparative prices and tax regimes. Methods: We calculate taxes and prices for three high‐income and three middle‐income countries. The data are drawn from the International Alcohol Control survey and from the Alcohol Environment Protocol. Tax systems are described and then the rates of tax on key products presented. Comparisons are made using the Purchasing Power Parity rates. The price and purchase data from each country's International Alcohol Control survey is then used to calculate the mean percentage of retail price paid in tax weighted by actual consumption. Results: Both ad valorem and specific per unit of alcohol taxation systems are represented among the six countries. The prices differ widely between countries even though presented in terms of Purchasing Power Parity. The percentage of tax in the final price also varies widely but is much lower than the 75% set by the World Health Organization as a goal for tobacco tax. Conclusion: There is considerable variation in tax systems and prices across countries. There is scope to increase taxation and this analysis provides comparable data, including the percentage of tax in final price, from some middle and high‐income countries for consideration in policy discussion.